Variation of Chromosome Composition in a Full-Sib Population Derived From 2x × 3x Interploidy Cross of Populus - Zhong, Yu-Hang; Zheng, Yun-Fei; Xue, Yin-Xuan; Wang, Lv-Ji; Zhang, Jin-Wang; Li, Dai-Li; Wang, Jun (Frontiers in Plant Science, 2022)
Interploidy cross commonly results in complex chromosome number and structural variations. In our previous study, a progeny with segregated ploidy levels was produced by an interploidy cross between diploid female parent Populus tomentosa × P. bolleana clone TB03 and triploid male parent P. alba × P. berolinensis ‘Yinzhong’. However, the chromosome compositions of aneuploid genotypes in the progeny were still unclear. In the present study, a microsatellite DNA allele counting—peak ratios (MAC-PR) method was employed to analyze allelic configurations of each genotype in order to clarify their chromosome compositions, while 45S rDNA fluorescence in situ hybridization (FISH) analysis was used to reveal the mechanism of chromosome number variation. Based on the MAC-PR analysis of 47 polymorphic simple sequence repeat (SSR) markers distributed across all 19 chromosomes of Populus, both chromosomal number and structural variations were detected for the progeny. In the progeny, 26 hypo-triploids, 1 hyper-triploid, 16 hypo-tetraploids, 10 tetraploids, and 5 hyper-tetraploids were found. A total of 13 putative structural variation events (duplications and/or deletions) were detected in 12 genotypes, involved in chromosomes 3, 6, 7, 14, 15, 16, and 18. 46.2% (6 events) structural variation events occurred on chromosome 6, suggesting that there probably is a chromosome breakpoint near the SSR loci of chromosome 6. Based on calculation of the allelic information, the transmission of paternal heterozygosity in the hypo-triploids, hyper-triploid, hypo-tetraploids, tetraploids, and hyper-tetraploids were 0.748, 0.887, 0.830, 0.833, and 0.836, respectively, indicating that the viable pollen gains of the male parent ‘Yinzhong’ were able to transmit high heterozygosity to progeny. Furthermore, 45S rDNA-FISH analysis showed that specific-chromosome segregation feature during meiosis and chromosome appointment in normal and fused daughter nuclei of telophase II of ‘Yinzhong’, which explained that the formation of aneuploids and tetraploids in the progeny could be attributed to imbalanced meiotic chromosomal segregation and division restitution of ‘Yinzhong’. The data of chromosomal composition and structural variation of each aneuploid in the full-sib progeny of TB03 × ‘Yinzhong’ lays a foundation for analyzing mechanisms of trait variation relying on chromosome or gene dosages in Populus.